Awareness and utilization of Geriatric Welfare Schemes among urban elderly population of District Gautam Budh Nagar - Agrawal, Deepika; Tyagi, Neha; Dhakar, Jagmohan Singh; Chaturvedi, Manish (Indian Journal of Community Health, 2019)
Background: India has 8.6% elderly population which is going to increase to 12% by 2025. Government of India is providing for the elderly through various social security and welfare schemes as well as legislations. But various studies, mostly in rural areas have shown that the awareness regarding these schemes was poor and incomplete. Utilization of schemes by the beneficiaries was even poorer. Very few studies have assessed the same in urban areas. Aims & Objectives: To assess the awareness and utilization of geriatric welfare schemes and factors associated with them among urban elderly. Material & Methods: The study was conducted in urban field practice area of Dept of Community Medicine, SMS&R, Greater Noida. 402 elderly living in slums of Bhangel, Noida, were interviewed using semi structured questionnaire assuming 50% awareness levels in the urban area with 10% relative precision and 95% confidence interval. Results: Awareness regarding any one scheme was 31.6%, of whom only one fourth subjects knew about more than one scheme. Among those who knew about the schemes, only 40% were utilizing them. The awareness as well as utilization was found to be significantly associated with religion, caste and educational status of the subject. Conclusion: The study shows poor awareness and even poorer utilization of geriatric welfare schemes among elderly people of urban slums. Further studies are required for judging the influencing factors.